Resurrecting the genus Enitharoides Brooks, 1953 (Heteroptera: Nepomorpha: Notonectidae): description of three new species and redescription of Enitharoides brasiliensis (Spinola, 1837), comb. nov. - Barbosa, Julianna Freires; Ribeiro, José Ricardo Inacio; Nessimian, Jorge Luiz (Zootaxa, 2017)
The subgenus Enitharoides Brooks, 1953 was erected to include two species of Enithares from South America with asymmetry in the male genital capsule: Enithares brasiliensis Spinola, 1837 and E. duidaensis Brooks, 1953. Enitharoides was elevated to genus in 1975, but neither it nor its species have been redescribed. Here the genus is redescribed, fixing the identity of the type-species as Enitharoides duidaensis, comb. nov. Members of this genus can be recognized by the triangular labrum, pronotum with anterolateral margins foveate, punctate scutellum, fore and middle legs with three tarsomeres, middle femur with an anteapical pointed protuberance, and an asymmetrical genital capsule. We transfer Enithares brasiliensis to Enitharoides; thus, Enitharoides brasiliensis is a new combination. A redescription of E. brasiliensis is given and three new species of Enitharoides are described from Brazil: E. lucasduquei Barbosa, Ribeiro & Nessimian, sp. nov. from Rio de Janeiro, E. tricomerus Barbosa, Ribeiro & Nessimian, sp. nov. from Espírito Santo and Minas Gerais, and E. lanemeloi Barbosa, Ribeiro & Nessimian, sp. nov. from Minas Gerais. A taxonomic key to the males of species of Enitharoides and a key to nymphs of the genera of Notonectidae occurring in Brazil are provided.